Nurses’ Knowledge and Practices on Influenza Vaccination for Pregnant Women - Sabty, Haila Malik; Dawood, Sundus Baqer; Tiryag, Ali Malik (Universitas Muhammadiyah Sidoarjo, 2024)
Influenza poses significant health risks to pregnant women, leading to increased morbidity and mortality rates compared to the general population. Despite the proven efficacy of the influenza vaccine in mitigating these risks, vaccination rates among pregnant women remain suboptimal. This study examines nurses' knowledge and attitudes regarding influenza vaccination for pregnant women within the AL-Zubair primary health sector in Basrah, Iraq, addressing the gap in understanding healthcare providers' roles in promoting vaccination. Prior research has highlighted the need for enhanced education and communication strategies among healthcare workers to improve vaccination uptake, yet specific data on nurses' knowledge in this context are limited. The study aims to assess nurses' knowledge, attitudes, and practices regarding influenza vaccination for pregnant women. Among the 88 surveyed nurses, a majority demonstrated adequate knowledge and favorable attitudes towards vaccination, with significant gaps in awareness regarding the consequences of influenza for newborns. Notably, 51.1% acknowledged the vaccine's utility in protecting pregnant women. This research provides crucial insights into the educational needs of nurses, which are essential for fostering effective patient education strategies. The findings underscore the importance of targeted educational interventions to enhance nurses' understanding of influenza vaccination, ultimately aiming to improve vaccination rates among pregnant women and reduce associated health risks.